Groundwater governance toolboxes to encourage sustainable water use - Meinzen-Dick, Ruth S. (CGIAR, 2023)
Always important, effective water governance is now vital as population growth and agricultural intensification increase the burden on our planet’s limited fresh water supplies. However, establishing sustainable, equitable, and effective rules for water use can be challenging even for surface water resources, such as lakes and rivers. When it comes to groundwater – which supplies more than 40 percent of irrigation globally – these challenges are multiplied.